Peran Guru Bidang Studi dalam Mendukung Pengelolaan Layanan Perpustakaan untuk Meningkatkan Literasi Membaca Siswa di SMP Negeri 7 Medan - Khairani, Alya; Maya Syafira Br Bangun; Dea Rosiah; Micha Milza Dinova; Juliana Br Pandiangan (JURNAL ILMIAH RESEARCH STUDENT, 2025)
This study aims to describe the role of subject teachers in supporting library service management to enhance students’ reading literacy at SMP Negeri 7 Medan. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The findings revealed that although the physical condition of the library is decent, its limited space and unsystematic organization hinder optimal use. The book collection is dominated by fiction, with a significant lack of non-fiction and academic resources. While literacy programs such as "Literacy Tuesday" are implemented, teacher involvement in designing and integrating literacy activities into daily lessons remains limited. Collaboration between teachers and librarians is not yet effective. Therefore, strengthening the role of teachers through training, active collaboration with librarians, and repositioning the library as a literacy center is essential for promoting a reading culture in schools.